Investigation of Heart Rate Variability and The Requirement for Vasopressors Relationship Due to Hypotension in Patients Undergoing Caesarean Section with Spinal Anesthesia - Bektaş, Kübra; Yücel, Duygu; Uğur, Fatih (Indonesian Journal of Anesthesiology and Reanimation, 2024)
Introduction: The most common effect of spinal anesthesia applied in cesarean section operations is hypotension. It is very important to prevent hypotension due to fetal bradycardia, acidosis, and maternal effects. Objective: This research was conducted to predict and prevent maternal hypotension in pregnant women undergoing elective cesarean section with spinal anesthesia by measuring heart rate variability parameters about hypotension. Methods: The study included pregnant women aged 18-45 with ASA 2 classification who underwent elective cesarean section with spinal anesthesia. Using the 'CorSense Heart Rate Variability Finger Sensor by Elite HRV' device and its smartphone application, 102 volunteer pregnant patients were monitored for 5 minutes in the recovery unit, and their data were recorded. After the administration of spinal anesthesia, patients who exhibited a decrease in systolic blood pressure of 20% or more from their baseline values received intravenous ephedrine in 10 mg bolus doses at each instance of low blood pressure measurements. Patients who received a total of 20 mg or more ephedrine doses or more as needed were designated as 'Group 1,' while patients who received less than 20 mg or no ephedrine were classified as 'Group 2.' Results: This study was completed with a total of 102 pregnant patients With 46 patients in Group 1 and 56 patients in Group 2, the relevant parameters that showed a statistically significant difference between patient groups were subjected to ROC analysis for predicting hypotension. It was determined that patients with high HF POWER and TOTAL POWER values had a greater need for vasopressors due to hypotension following spinal anesthesia (p<0.05). Conclusion: In the research, these values are believed to have the potential to predict hypotension in patients undergoing cesarean sections with spinal anesthesia.